The Surface Mining Control And Reclamation Act Of 1977 (Public Law 95-97) - A Look At Some Impacts On Coal Production Costs - James A. Curry (Society for Mining, Metallurgy & Exploration, 1980)
Table I identifies the maximum cost of the individual provisions with spoil disposal in Appalachia leading at $3.98 per ton, This was followed by deep mine subsidence control and monitoring at $1.66 per ton. At the request of the U.S. Department of Energy, the Bowser-Morner Testing Laboratories of Dayton, Ohio, evaluated Consol's cost estimates for 14 of the 21 regulatory provisions the company studied. It is interesting to note that Bowser-Morner concluded that Consol's estimates of costs were very conservative and that the actual costs will be substantially higher than what the company reported. In 1978 a joint committee of the National Coal Association and the American Mining Congress made estimates of cost impacts under 11 OSM permanent rules (see Table II). Six rules applied to mid-western strip mining were projected to cost $6.52 to $17.17 per ton. Five rules applied to mid-western strip mines showed costs ranging from $.91 to $6.11 per ton. Three rules applied to deep mines (regardless of region) were seen raising costs from $ .57 to $2.67 per ton. The joint committee reported trouble developing overall figures because member firms used widely different assumptions in calculating their costs. That same statement could no doubt be made when comparing most cost data available today.